2011
DOI: 10.1007/s10661-011-2191-7
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals: their pathway from the ground, groundwater and springs to Lake Góreckie (Poland)

Abstract: The migration pathways of heavy metals derived from an area previously in agricultural use was investigated in the Wielkopolski National Park (mid-western Poland). The heavy metals involved (Cd, Cu, Cr, Pb, Ni and Zn) were determined in groundwater, the springs that feed Lake Góreckie and the lake itself. In order to show how the heavy metals may be set free and what is their biological availability, soil and sediment samples were subjected to single-stage extraction, using 0.01 M CaCl(2), 0.02 M EDTA, 0.005 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Although some authors compare Mehlich 3 to other extractants (Bortolon and Gianello 2012;García et al 1997;Liu et al 2011;Ostatek-Boczynski and Lee-Steere 2012;Rodriguez-Suarez et al 2007) and a few authors have run extraction of metals from soil with 1 M HCl (Bakircioglu, Kurtulus, andİbar 2011;Cekstere and Osvalde 2013;Kuang et al 2013;Loide, Noges, and Rebane 2005;Korzeniowska 2010, Walna andSiepak 2012;Walworth, Gavlak, and Panciera 1992), the literature lacks reports comparing both methods. However, researchers often detect strong correlations between M3 and such extractants as DTPA (Cancela, Aparecida De Abreu, and Paz-González 2002;Chilimba, Mughogho, and Wendtc 1999;Brennan et al 2008 EDTA (Brennan et al 2008), or 0.1 M HCl (Bortolon and Gianello 2012;Fonseca, Caires, and Barth 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although some authors compare Mehlich 3 to other extractants (Bortolon and Gianello 2012;García et al 1997;Liu et al 2011;Ostatek-Boczynski and Lee-Steere 2012;Rodriguez-Suarez et al 2007) and a few authors have run extraction of metals from soil with 1 M HCl (Bakircioglu, Kurtulus, andİbar 2011;Cekstere and Osvalde 2013;Kuang et al 2013;Loide, Noges, and Rebane 2005;Korzeniowska 2010, Walna andSiepak 2012;Walworth, Gavlak, and Panciera 1992), the literature lacks reports comparing both methods. However, researchers often detect strong correlations between M3 and such extractants as DTPA (Cancela, Aparecida De Abreu, and Paz-González 2002;Chilimba, Mughogho, and Wendtc 1999;Brennan et al 2008 EDTA (Brennan et al 2008), or 0.1 M HCl (Bortolon and Gianello 2012;Fonseca, Caires, and Barth 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Trace elements penetrate to surface waters from natural and anthropogenic sources (Krishna et al 2009; Férauda et al 2009; Zhao et al 2011; Walna and Siepak 2012; Zeng et al 2015). In non-contaminated water reservoirs, the concentrations of most trace elements are low and originate mainly from the weathering of parent rock and soil (Reza and Singh 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As the present research has demonstrated, these are primarily areas in the drainage basins of the Pliszka and Ołobok rivers (the Lake Niesłysz region). The variability of selected heavy metals in spring water was already found not only in the Gry_ zynka river catchment of the Lubuska Upland in the previous work (Szczucińska et al 2010) but also in springs near Poznań in western Poland (Walna and Siepak 2012). Walna and Siepak (2012) interpret the variability as caused by both natural processes (long-lasting precipitation that allows for immobile forms of trace elements to become mobile; changes in pH) and anthropogenic factors (mainly agriculture).…”
Section: Trace Element Variability In Spring Watermentioning
confidence: 61%
“…The mosaic phenomenon of spatial and temporal variation of iron content in the spring waters was also observed by Mazurek et al (2014). Particularly, changes caused by the variability in pH and in the redox potential (Walna and Siepak 2012) are important. In the studied springs, the occurrence of moderate redox conditions (averaging 424 mV) is conducive to the water migration of iron and manganese.…”
Section: Trace Element Variability In Spring Watermentioning
confidence: 99%
See 1 more Smart Citation